Changes in Distribution Patterns for Larimichthys polyactis in Response to Multiple Pressures in the Bohai Sea Over the Past Four Decades - Han, Qingpeng; Shan, Xiujuan; Jin, Xianshi; Gorfine, Harry; Chen, Yunlong; Su, Chengcheng (Frontiers in Marine Science, 2022)
Understanding patterns of distribution changes of species in their critical habitats is important for analyzing population dynamics and their adaptive response to environmental change. Here, we developed eight alternative spatio-temporal models for small yellow croaker (Larimichthys polyactis), which were fitted to data from bottom trawl surveys in the Bohai Sea conducted each spring (spawning period) and summer during 1982–2018. These models included different combinations of the effects of local sea temperature, fishing pressure, and individual climate pressure index (e.g., North Pacific index, NPI), with the most parsimonious model based on Akaike’s Information Criterion (AIC) identified as the optimal model for each season. The model based solely on the effect of the individual climate index was used for pre-analysis, i.e. the base model, and the climate index in the model with the lowest AIC was selected for each season. In spring, a spatio-temporal model with a quadratic effect of sea temperature, plus the spatially-varying effects of the NPI and fishing pressure was selected, as the AIC value of this model was reduced by 41.491 compared to the model without these effects. In the summer after spawning, the spatio-temporal model with West Pacific index (WPI) as a climate index covariate lagged by 1-year best explained the spatio-temporal distribution patterns of the stock based on the AIC. The results suggested that the small yellow croaker significantly decreased in biomass in the Bohai Sea over the study period. A statistically significant northeastward shift in the center of gravity (COG) and a contraction in the distribution range of small yellow croaker occurred in summer throughout the study period (p<0.05). During the partial study period in spring (1993–2018), a statistically significant northeastward shift in the COG was also found (p<0.05). Our results showed that biomass-density hotspots of small yellow croaker in both seasons have shrunk or disappeared in recent years. Overall, the stock in their spawning, feeding and nursery grounds over the past 40 years have been influenced by multiple pressures, and the density of the stock in the southwestern areas of the Bohai Sea declined faster and more drastically than that in the northeastern areas.